Genetics: Is LADA just late onset type 1 diabetes? - Hernández, M.; Nóvoa-Medina, Y.; Faner, R.; Palou, E.; Esquerda, A.; Castelblanco, E.; Wägner, A. M.; Mauricio, D. (Frontiers in Endocrinology, 2022)
Background There is a controversy regarding Latent Autoimmune Diabetes in Adults (LADA) classification and whether it should be considered a slowly progressing form of type 1 (T1) diabetes (DM) or a distinct type of DM altogether. Methods This cross-sectional study assessed major genes associated with T1DM (class II HLA, PTPN22 [rs2476601] and INS [rs689]) in patients with LADA, as compared with participants with T1DM (stratified according to age of diagnosis before or after 30) and T2DM. HLA genotyping of the DRB1, DQA1 and DQB1 loci was performed by reverse PCR sequence-specific oligonucleotides. HLA haplotypes were assigned according to those most frequently described in the European population. INS and PTPN22 SNPs were genotyped by real-time PCR. Results A total of 578 participants were included: 248 with T1DM (70 diagnosed after the age of 30), 256 with T2DM and 74 with LADA. High risk HLA alleles were significantly more frequent in LADA than in T2DM, whereas the opposite was true for protective alleles. We found a lower frequency of the high-risk DRB1*04-DQB1*03:02-DQA1*03:01 haplotype in LADA (21.1%) than in the overall T1DM (34.7%) (p<0.05), whereas no differences were found between these groups for DRB1*03-DQB1*02:01-DQA1*05:01 or for protective alleles. Only 12% the overall T1DM group had no risk alleles vs 30% of LADA (p<0.0005). However, HLA allele distribution was similar in LADA and T1DM diagnosed after the age of 30. A total of 506 individuals (195 with T1DM [21 diagnosed after age 30] 253 with T2DM and 58 with LADA) were genotyped for the PTPN22 and INS SNPs. The G/A genotype of the PTPN22 rs2476601 was more frequent and the T/T genotype of the INS SNP rs689 was less frequent in T1DM compared to LADA. We did not find any significant differences in the frequency of the mentioned SNPs between LADA and T2DM, or between LADA and T1DM diagnosed after the age of 30. Conclusion In this relatively small cross-sectional study, the genetic profile of subjects with LADA showed a similar T1DM-related risk allele distribution as in participants with T1DM diagnosed after the age of 30, but fewer risk alleles than those diagnosed before 30. Differences were present for HLA, as well as PTPN22 and INS genes.